e-EduTour: The Digital International Student Mobility Multi-Module - Soubakeavathi, Rethinasamy; Soo, Ruey Shing; Nurul Huzaimah, Hussien; Keezrawati, Mujan Yusuf; Liyana, Rosli; Joseph, Ramanair (UMK, 2022)
e-EduTour is a digital international student mobility module co-created by lecturers and undergraduates taking the English for Global Communication and Strategic Communication degree programmes at the Faculty of Language and Communication, Universiti Malaysia Sarawak (UNIMAS). Objectives: 1. provide fun and meaningful learning experience for undergraduate students, 2. offer international student mobility experience digitally. The module contributes towards UNIMAS’ aspiration as “Community Driven University” by collaborating with schools in Sarawak and strengthening partnership with international partner universities, and industry.